Induksi Kalus Dari Eksplan Daun Tanaman Kawista (Limonia acidissima L.) Secara In Vitro Pada Media MS Dengan Penambahan Beberapa Konsentrasi Air Kelapa (Cocos nucifera L.) - Eka Saptiani; Hayatul Rahmi; Muharam (Jurnal Agrotek Indonesia (Indonesian Journal of Agrotech), 2020)
This research was conducted to find out the best effect from the consentration of coconut water to growth of kawista leaf explant (Limonia acidissima L.) with tissue culture methods. Research done in the laboratory of faculty of Agriculture of Singaperbangsa University. The method of research used experimental method, using a single Completely Randomized Design (CRD). Consisting of 12 treatments of coconut water, namely A control 0%, B 10%, C 20%, D 30%, E 40%, F 50%, G 60%, H 70%, I 80%, J 90%, K 100%, and L 10 ppm NAA+0,1 ppm BAP, each treatment with 3 replications. The results showed significant test done DMRT (Duncan Multiple Range Test) standard of 5%. The results showed that administration of coconut water significantly affected the percentage of callus growth, callus emergence and callus weight. The best treatment was with a treatment I (80%) with 100% growth percentage, and give callus weight of 1,22 gram. Treatment D (30%) give fastest callus growth time is 9 hsi.